A CRITIC-BPNN APPROACH TO FRICTION STIR WELDING PARAMETRIC SELECTION AND PREDICTION USING AA6082-T6 MATERIAL - Mufutau Adeniyi Abolarin; Adeyinka Oluwo; John Rajan; Swaminathan Jose; Sunday Ayoola Oke |; Alexander Iwodi Agada; Ayomide Sunday Ibitoye (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
The uncontrolled friction stir welding heat generation impacts the quality of welds. However, the intuition and experience of the engineer fail to regulate the effects of excessive heat generation on the weld quality and research has not addressed this aspect yet. This paper fills the gap by introducing an integrated CRITIC-BPNN (CRiteria Importance Through Intercriteria Correlation-Back Propagation Neural Network) method to investigate the selection and optimisation characteristics of the friction stir welding process for AA6082-T6 material. In this study, two major performance characteristics i.e. ultimate tensile strength (UTS) and percentage elongation (%EL), were chosen for analysis. The input parameters for the machining were the tool rotational speed, welding speed, tool pin profile and tool shoulder diameter. For the back propagation neural network model, a four-layer network with sigmoid hidden neurons and output neurons was selected. The weight estimates of the friction stir welding parameters are determined by the CRITIC method. For further weight determination between the nodes and edges of the neural networks, the Poisson distribution model was introduced. This stochastic-based method was used to calculate the weights at the edges, between the inputs, hidden layers and outputs of the neural network. The forward pass and backward passes are then used for updating and error minimisation. The welding speed has the highest weight with a contribution of 49.72% using the CRITIC method, implying that welding speed is the best and most influential parameter of the friction stir welding process. For the 4-1-2 neural network architecture, the values of the ultimate tensile strength and percentage elongation at the optimal thresholds are 0.6457 and 0.6019, respectively, for the first forward pass and 0.6123 and 0.6356, respectively, for the second forward pass. The predicted tensile strength is 320.64 MPa and the prediction for the percentage elongation is 18.83%. The results obtained from the proposed method could be useful for planning purposes during the friction welding process.